Pengaruh Citra Merek dan Pemasaran Digital melalui Hubungan Pemasaran pada Keputusan Pembelian Apotek di Kota Bandung - Andi Gunawan; Wentri Merdiani (Lembaga Yasin AlSys, 2025)
The increasingly intense competition in the pharmacy industry, particularly in urban areas such as Bandung, demands that business actors adopt effective marketing strategies to attract and retain customers. This study aims to analyze the influence of brand image, digital marketing, and relationship marketing on consumer purchasing decisions in pharmacies across Bandung. A quantitative approach was employed, with data collected through surveys and statistical analysis used to examine the relationships among variables. Respondents consisted of pharmacy consumers located throughout Bandung. The analysis revealed that consumer perceptions of brand image (index score: 74), digital marketing (72), and relationship marketing (76) were within the high to moderate categories, while the purchase decision index stood at 71. Brand image had a significant influence on relationship marketing, accounting for 52.1%. Additionally, digital marketing contributed 29.2% and relationship marketing 30.5% to purchasing decisions. The indirect effects of brand image and digital marketing via relationship marketing were found to be greater than their direct effects. These findings confirm that relationship marketing significantly mediates the influence of brand image and digital marketing on purchasing decisions. Therefore, building trust through strengthening brand image, optimizing digital media, and fostering personalized consumer relationships are key strategies for enhancing loyalty and purchase decisions in the pharmacy sector.